Radar signals - Levanon, Nadav (J. Wiley, 2004)
A text and general reference on the design and analysis of radar signals As radar technology evolves to encompass a growing spectrum of applications in military, aerospace, automotive, and other sectors, innovations in digital signal processing have risen to meet the demand. Presenting a long overdue, up-to-date, dedicated resource on radar signals, the authors fill a critical gap in radar technology literature. Radar Signals features in-depth coverage of the most prevalent classical and modern radar signals used today, as well as new signal concepts developed in recent years. Inclusion of key MATLAB software codes throughout the book demonstrates how they dramatically simplify the process of describing and analyzing complex signals. Topics covered include: Matched filter and ambiguity function concepts Basic radar signals, with both analytical and numerical analysis Frequency modulated and phase-coded pulses Complete discussion of band-limiting schemes Coherent LFM pulse trains-the most popular radar signal Diversity in pulse trains, including stepped frequency pulses Continuous-wave signals Multicarrier phase-coded signals Combining lucid explanation, preferred signal tables, MATLAB codes, and problem sets in each chapter, Radar Signals is an essential reference for professionals-and a systematic tutorial for any seeking to broaden their knowledge base in this dynamic field.